Kerukunan Umat Beragama Di Desa Bedali Kecamatan Ngancar Kabupaten Kediri Provinsi Jawa Timur - Safingin, Agus; Suka Arjawa, I Gst Putu Bagus; Sastri Mahadewi, Ni Made Anggita (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 1 No 2 (2019), 2020)
ABSTRACT Diversity is something that cannot be avoided by anyone, therefore there is no other choice for humans to accept the diversity that exists and direct it for the common good. Diversity is spread throughout the region in Indonesia one of them in the Village Bedali District Ngancar District of Kediri, East Java Province. This study uses the functional structural theory of Talcott Parson in the AGIL scheme (adaptation, goall attaiten, integration and latency) then supported by a derivative system that is a system of social action. The form of religious harmony in Bedali Village is the high tolerance of the community. In this research, tolerance is divided into three fields, namely social culture, religion and education. While the efforts made by the community are by increasing interaction between fellow citizens, mutual cooperation in various fields and mutual respect. Key words : Religion Harmony, the form of harmony, efforts to maintain harmony